Current Ratio and Debt to Equity Ratio as Determinants of Return on Equity in Food and Beverage Companies - Zulkifli, Zulkifli; Febriyantoro, Mohamad Trio (International Journal of Business, Law, and Education, 2025)
This study investigates the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX). The population consists of 95 companies in 2023. Using purposive sampling, 26 companies were selected based on criteria such as consistent listing and publication of audited annual financial reports from 2020 to 2023. CR and DER are the independent variables, while ROE is the dependent variable. Panel data regression analysis was conducted using EViews software. The results show that CR and DER simultaneously have a significant effect on ROE. However, partially, CR does not significantly affect ROE, while DER has a negative and significant impact. This suggests that companies should manage their debt levels carefully, as excessive reliance on debt can reduce returns to shareholders. For investors, DER is a crucial indicator for evaluating financial risk and assessing a company's capital structure before making investment decisions.